Gestão administrativa na Educação Superior: proposta de Secretaria Integrada de Atendimento à Graduação (SIAG), no CCHLA-UFPB - Silva, Givanildo da (2018)
Budgetary crisis and constant personnel renewal have posed challenges to efficiently and effectively service students at the Humanities Center (CCHLA) of Federal University of Paraíba (UFPB). One of the alternatives has been the standardization of administrative procedures through an online system for academic activity management (SIGAA), which is a module of a wider platform (SIG) acquired from the Federal University of Rio Grande do Norte (UFRN). The use of this system abides by Brazilian legislation (Law no. 13.726 / 2018, Decree n. 9,094 / 2017) as well as by the current development plan of the university (PDI / UFPB 2014-2018). The objective of this research was to analyze the management model of an integrated secretariat (SIAG) of another academic unity of UFPB (CCTA – Communication, Tourism and Arts Center) and use it as a parameter to develop a similar model for CCHLA. The study was carried out through an exploratory, qualitative research, having as data collection techniques: i) direct observation, ii) documentary research, iii) interview with staff (managers, coordinators and clerks), and iv) closed questionnaire with undergraduate students serviced by SIAG / CCTA. Data were treated through triangulation and confronted with the theoretical views of authors who approaches public management. Results revealed that SIAG/CCTA has been efficient and effective and meets its purposes. It is well accepted by its target audience, i.e., civil servants and students, despite some considerations made by users which were collected from direct observation. In view of the results, a proposal of a SIAG for CCHLA was drawn up, adapting it to its own reality and strengthening positive aspects to correct failures.